Intrathoracic migration of ventriculoperitoneal shunt through the Morgagni's hernia in case with Down syndrome: A rare shunt complication - Cakin, Hakan; Kaplan, Metin; Ozturk, Sait; Kazez, Ahmet (Medknow Publications & Media Pvt Ltd, 2013)
[Abstract Not Available]